Application of Albert Bandura Social Learning Theory in PAI Learning at Al-Wafa Ciwidey SMP Bandung - Lestari, Sri Rahayu; Nurjanah, Siti; Indriani, Wiwik (Lembaga Yasin AlSys, 2021)
This article discusses the application of social learning theory which aims to determine the application of the social concept of the Albert Bandura theory at Al-Wafa Ciwidey Junior High School in Bandung, the supporting factors for the application of the Albert Bandura social learning theory at Al-Wafa Ciwidey Middle School Bandung, the inhibiting factors for the application of Albert Bandura social learning theory at SMP Al-Wafa Ciwidey Bandung. This type of research is a qualitative descriptive with a phenomonological approach. Retrieval of data through the method of observation, interviews. The data source is the teacher of Islamic religious education subjects. After that, it is analyzed by drawing conclusions. The results of this study, the application of social learning theory with the concept of modeling principles in Islamic religious education learning at Al-Wafa Middle School have been applied to aspects of attention, retention, production, and motivation. And the supporting factor in the application of social learning theory is the ability of teachers which includes pedagogic, professional, personal and social skills in guiding, directing and encouraging students to be active during the learning process as well as interesting learning media. While the inhibiting factor is the low motivation of students to learn and less varied learning media. The impact of the application of social learning theory at SMP Al-Wafa Ciwidey Bandung is that students become more ready to learn because at the initial stage the attention stage has been carried out. Then finally students become more motivated because of the reward and punishment system and usually students will be more motivated when learning is packaged in activities such as games.